To find the equation, use the slope intercept form:
y = mx + b
where m is the slope and b is the y-intercept
Take the points on the graph:
(x1, y1) ==> (3, -4)
(x2, y2) ==> (0, -2)
Find the slope using the formula below:
The y-intercept is the point where the line crosses the y-axis.
The y-intercept here is -2.
Therefore, we have the equation:
Now, equate the equation above to zero:
Multiply through by -3, to eliminate the fraction:
Therefore, the equation that represents the graph is:
3y + 2x + 6 = 0
ANSWER:
A) 3y + 2x + 6 = 0